PERANAN CORPORATE IMAGE UNTUK MENINGKATKAN KEPUASAN PELANGGAN PT L’OREAL INDONESIA CABANG BANJARMASIN - Diana Hayati; Penta Lestarini Budiati; - Renny (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2019)
Abstract, The purpose of this study was to determine how the role of Corporate Image to increase customer satisfaction at PT L’Oreal Indonesia Banjarmasin Branch. The method used in this research is descriptive method. The study population was all customers who purchased L’Oreal products as many as 611 customers, with a total sample of 100 people taken randomly from the population. The results showed that PT L'Oreal Indonesia Banjarmasin Branch had not run an advertising strategy optimally, still did not implement public relations well, did not provide physical and non-physical identities to its products, word of mouth communication was quite effective and had not provided non-personal stimulation .